Interventions to reduce relapse risk and drug craving in patients with substance use disorders in forensic psychiatric care: a systematic review of controlled trials - Månsson, Martin; Andiné, Peter; Hildebrand Karlén, Malin; Holmberg, Christopher (Frontiers in Psychiatry, 2025)
Systematic review registrationSubstance use is a risk factor for relapse in violent crime. In forensic psychiatric care (FPC), severe mental disorder and comorbid substance use is common, with a majority having a history of substance use disorder (SUD) and many having committed their index crime while under influence. FPC is dedicated to treating these patients to reduce the risk of criminal recidivism. Though interventions for SUD are used, none of them have been developed to meet the needs of the FPC patient group specifically.AimTo identify and evaluate controlled interventions that primarily or secondarily reduce the risk of relapse into substance use and/or feelings of drug craving among FPC patients.MethodsA systematic review was conducted, spanning 10 years (2014-2024). The PRISMA 2020 guidelines were followed. A PICO framework, and specified inclusion and exclusion criteria, guided the process. In collaboration with an experienced medical librarian a search strategy was developed and searches were conducted in MEDLINE, Embase, and PsycInfo. Blinded screening and article selection through consensus voting was performed collaboratively by two of the authors, as was the full-text reviews. Quality assessment was conducted using the CASP checklist for controlled studies. The results were synthesized using vote counting to determine the direction of effect across studies, following the SWiM reporting criteria.ResultsThe searches identified 1275 articles. After deduplication, 750 articles remained. Following screening, 9 articles were assessed in full, of these, 4 were excluded for reporting irrelevant outcomes and 3 for lacking a control group. Finally, 2 controlled trials – both RCTs – were included. Overall quality was adequate with some concerns for bias. No conclusive evidence of a treatment effect on SUD measurements was reported.ConclusionThis systematic review suggests there is a lack of research aimed at the study of SUD interventions within FPC. Analysis of included articles found no conclusive evidence of effective treatments, but there seems to be an indication of a beneficial effect on drug use in one study, a treatment that addresses impulsivity. Further high-quality studies better tailored to FPC are needed to evaluate SUD treatment outcome among FPC patients.